A Guide to Early Years Practice - Smidt, Sandra, 1943- (London : RoutledgeFalmer, 2002)
Smidt offers early years and nursery practitioners complete guidance on inspections and on how to meet the government's desirable outcomes. She also discusses how to support and extend learning in all early years settings.
Previous ed.: 1998.
Includes bibliographical references and index.
Keywords: Education, Preschool -- Great Britain; Preschool teaching -- Great Britain; Child development -- Great Britain; Education